Current Perspectives on Anorexia Nervosa in Health and Therapy - a review - Bieńkowski, Wojciech; Charkot, Julia; Kusy, Bartłomiej; Bieńkowski, Michał; Charkot, Mikołaj; Kucharczyk, Piotr; Jaszczuk , Irmina; Retman , Patrycja (Quality in Sport, 2025)
Introduction and purpose: Anorexia nervosa is a serious mental disorder characterized by persistent food restriction, intense fear of gaining weight, and distorted body image. Despite decades of research, anorexia remains challenging to diagnose and treat due to its complex psychological, social, and biological roots. This review aims to summarize current knowledge on anorexia nervosa, focusing on updated diagnostic criteria, risk factors, treatment strategies, and emerging trends in therapy and healthcare. Material and method: A narrative literature review was conducted using publications from 2010 to 2024, sourced from databases such as PubMed, Scopus, and Web of Science. Inclusion criteria covered peer-reviewed articles on the epidemiology, diagnosis, treatment, and neurobiological or psychosocial aspects of anorexia nervosa. Studies were selected based on relevance, methodological quality, and applicability to adolescent and adult populations. Results: The review highlights significant developments in understanding anorexia nervosa. Diagnostic updates in DSM-5 and ICD-11 have influenced prevalence estimates. Risk factors include genetic predisposition, personality traits, and sociocultural pressures. Contemporary treatments integrate psychotherapies (CBT-E, FBT, ACT), digital interventions, and pharmacotherapy. Barriers such as stigma, late diagnosis, and insufficient specialist care persist. Emerging research explores neurobiology, executive functioning, and circadian rhythms. Conclusions: Anorexia nervosa is a multifactorial disorder requiring interdisciplinary approaches. Advances in diagnosis and treatment must be supported by greater public awareness, early intervention, and integration of educational and therapeutic strategies. Further research is needed to personalize care and improve long-term outcomes.